Liquid and solid phase microextraction methods for the analysis of organic environmental pollutants - Loh, Saw Hong (Johor: Universiti Teknologi Malaysia, 2014)
This work involves the investigation of new approaches and applications in miniaturized sample preparation techniques based on liquid phase and solid phase microextractions. A two-phase hollow fiber liquid phase microextraction (HFLPME) method combined with gas chromatography-mass spectrometry was developed for the determination of selected polycyclic aromatic hydrocarbons (PAHs) in fresh milk.